Safety and Efficacy of Cangrelor Among Three Antiplatelet Regimens During Stent-Assisted Endovascular Treatment of Unruptured Intracranial Aneurysm: A Single-Center Retrospective Study - Cheddad El Aouni, Mourad; Magro, Elsa; Abdelrady, Mohamed; Nonent, Michel; Gentric, Jean Christophe; Ognard, Julien (Frontiers in Neurology, 2022)
Introduction Thromboembolic events represent the most frequent complications of endovascular treatment of unruptured intracranial aneurysm using stent-assisted coilling or flow diverter stents. Dual antiplatelet therapy has become the standard to prevent these but remains unstandardized. We present here a single center experience of 3 standardized antiplatelet regimens during brain aneurysm treatment, while emphasizing the use of the Cangrelor. Method We retrospectively reviewed data from patients treated using stent-assisted coilling or flow diverter stents from 2016 to 2021. We collected and compared safety and efficacy data within 6 months of three groups of patients corresponding to three antiplatelet standardized regimens: group T with Ticagrelor, with preprocedural preparation; group E with Eptifibatide, injected during procedure; group C with Cangrelor, injected during procedure. Results Data of 112 patients were analyzed and 76 belonged to group T, 21 to group E, and 15 to group C. Eleven events over the 14 recorded were adjudicated to be related to antiplatelets, their repartition did not differ between the 3 groups (p = 0.43). All symptomatic events (N = 8) were not distributed significantly differently between the 3 groups (p = 0.11) and asymptomatic events were also balanced (p = 1.00). Of these, 6 subjects had a change in the mRS score at 3–6 months. Thrombo-embolic events represented the most encountered events in the sample: 2 acute ischemic strokes were recorded in group E and 1 in group T; 1 transient ischemic stroke was noted in group E; 4 silent infarcts were found on control MRI (2 belonged to group T, 1 to group E and 1 to group C). Among 3 intracranial bleeding events, 1 was symptomatic in group C, 2 were asymptomatic in group T. On the control evaluation performed at 6 months, there was no significant difference on aneurysmal occlusion (p = 0.67). Conclusion This single-center retrospective study compared 3 antiplatelet regimens, finding no significant difference in the safety and efficacy in the context of endovascular treatments of unruptured aneurysm using stent or flow diverters. This study adds data for the Cangrelor use and suggests its usefulness in the field of neuro-endovascular intervention. Randomized controlled studies are warranted to confirm these results.